Assessment of ventilation in elderly care centres - Cerqueira, F. (2014)
The users of Elderly Care Centres (ECC) often spend all their time inside the premises. Therefore, their exposure to poor indoor air quality (IAQ) is likely to affect their health. Ventilation is a recognized technique to improve IAQ which is expected to have a significant influence on building occupant´s health. The need for studies on the relation between building´s physical characteristics and the indoor environment in ECC led an interdisciplinary team of researchers to develop the project GERIA, funded by the Portuguese Foundation for Science and Technology (FCT). The project objectives are to study the physical and ventilation characteristics of the buildings, the indoor air quality and the elderly people health. As part of the project, 33 private institutions for social care, located in the urban area of Lisbon, were randomly selected and invited to participate. In every ECC the characteristics of the building were recorded in a survey and measurements of the indoor air temperature, relative humidity and CO2 concentration were carried out. Measurements were carried out at two rooms (at least). As the indoor air of these rooms was not affected by combustion appliances, CO2 emissions were considered as a surrogate marker of human body emissions. In a relevant number of cases it was possible to use indoor CO2 concentration to estimate the average ventilation rate based on tracer gas constant emission method (during occupancy period) and based on tracer gas decay method (when occupants left the rooms). It is concluded that 70% of the maximum CO2 concentration in rooms is above 1250 ppm. Furthermore, the estimated ventilation rate is below 0.4 h-1 in 30% of the rooms. Opening the windows and/or doors when leaving the room increases ventilation rate above 1.0 h-1 in 50% of the rooms. In this communication the impact of pollutants emitted by human breath in indoor environment of elderly cares and estimated ventilation rates will be studied, analysing the concentration of carbon dioxide (CO2) in sleeping rooms.